Authentic Assessment Innovation for Speaking Skills in The Grade 10 Arabic Language Book of The Merdeka Curriculum - Tomi Fitrawan; R. Umi Baroroh; Oktavia Dwi Lestari; Khaerul Muttakin (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
This study addresses the mismatch between communicative-competence goals and structurally oriented assessment practices in Arabic-speaking (kalām) evaluation at Madrasah Aliyah. In line with the Merdeka Curriculum, which emphasizes contextual and performance-based learning, the research aims to develop an authentic assessment model integrated into Grade X Arabic textbooks. Using a Research and Development (R&D) approach with the 4D model (Define, Design, Develop), the study began with a content analysis of speaking activities and existing assessment components to identify conceptual and pedagogical gaps. Based on these findings, an innovative assessment framework was designed by aligning textbook themes with authentic communicative tasks and analytically developed speaking rubrics. The resulting model integrates contextual simulations, oral presentations, and narrative tasks assessed through indicators such as fluency, pronunciation accuracy, lexical relevance, structural adequacy, meaning clarity, and communicative confidence. The findings indicate that this model provides a systematic and coherent approach to assessing speaking skills, moving beyond fragmented, form-focused evaluations. This study contributes a theory-based, practical framework for authentic speaking assessment that operationalizes the principles of the Merdeka Curriculum and supports more meaningful evaluation of communicative language.